2021
DOI: 10.1088/1361-648x/abdb12
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of sp–d exchange constants revisited

Abstract: We present a new computational method for estimating the sp–d exchange constant, J eff s p − d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 40 publications
(72 reference statements)
2
5
0
Order By: Relevance
“…Similar magnetic behaviors were also found in some dilute magnetic semiconductor materials. [ 36 ] Sarkar et al reported room temperature antiferromagnetic of Nd 1.90 Co 0.10 O 3− δ nanocrystalline and confirmed that the antiferromagnetic to ferromagnetic phase transition occurs at about 100 K. [ 28 ] Fe x Cr 2− x O 3 nanoparticles were reported to have the same magnetic transition and confirmed that oxygen defects are a key factor to induce magnetic behavior by the bound magnetic polaritons (BMP) model. [ 37 ] In Figure 4, the BMP model is applied to further analyze the origin of the magnetic transition.…”
Section: Resultsmentioning
confidence: 98%
“…Similar magnetic behaviors were also found in some dilute magnetic semiconductor materials. [ 36 ] Sarkar et al reported room temperature antiferromagnetic of Nd 1.90 Co 0.10 O 3− δ nanocrystalline and confirmed that the antiferromagnetic to ferromagnetic phase transition occurs at about 100 K. [ 28 ] Fe x Cr 2− x O 3 nanoparticles were reported to have the same magnetic transition and confirmed that oxygen defects are a key factor to induce magnetic behavior by the bound magnetic polaritons (BMP) model. [ 37 ] In Figure 4, the BMP model is applied to further analyze the origin of the magnetic transition.…”
Section: Resultsmentioning
confidence: 98%
“…Correspondingly, the right panel of figure 4 shows the dependence of E (n,σ) H on the band gap value, e (n,σ) gap . Similar plots have also been found for the systems Ga(TM n )N, TM = Ti, V, Cr, Fe, Ni. In view of our previous reports (see, for example, reference [20] and references therein), the left panel of figure 4 describes the local aspect of the doping process. On the other hand, the right panel of figure 4 describes the holistic view of the doping.…”
Section: The Effect Of the Magnetic Doping On The Band Gapmentioning
confidence: 96%
“…In equation ( 9), C( f d , f an ) is a factor depending on the band fillings of megatom and host anions; e dX is the d-band center of the d-bands of the dopant formation of the megatom; e p,an is the p-band center of the p-bands of the anions of the system and V dX,sp is the coupling between the cations of the megatom and the host anions. The latter can be approximated by the sp-d magnetic coupling, J sp-d , between the d-band of the megatom and the host anions [24]. Variations, δM tot (correspondingly, variations δe gap ), will affect the megatom's orbital energies e dX (expressed, for example, within a Hubbard-U term, ≈ U M ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we proposed a new computational method for specifying the GK-product [104,117,118]. It is based on the response properties of the doped system in the imposed boundary condition on magnetization density, M, of the system.…”
Section: Goodenough-kanamori Rulesmentioning
confidence: 99%